Dampak Sosialisasi Perpajakan Bagi Pemilik Usaha Pada Sektor Usaha Mikro Dan Kecil: Faktor Pemahaman Dan Kepatuhan Pajak - Andi Aziz Herlambang (Universitas Multimedia Nusantara, 2018)
This research is using qualitative research method with interpretive paradigm and phenomenogist approach that aims to know and explain the impact of tax socialization for Micro dan Small Business sector (MSE) owner in improving the understanding and compliance of SME sector tax and understanding of tax amnesty along with business owners’ compliance. Informants were selected randomly with the criteria of the micro and small sectors present in the printing industry in Kecamatan Cilandak, South Jakarta. In addition, the Extension Section of KPP Pratama Jakarta Cilandak is used as supporting informant to process triangulation of information obtained from the business owner. All datas were obtained through direct interview techniques, with the addition of observation and documentation techniques for specific informants. The results of this research prove that the socialization of taxation can provide an impact for increased understanding of SME sector tax and business owners’ compliance of taxes along with tax amnesty. Although for some informants there are still some reasons or motives that sometimes hinder the impact, accompanied by an indirect impact on factors which are not directly experienced by certain informants.